The Relationship Between Physical Factors and Architecture of Rehabilitation Educational Care Centers With the Quality of Rehabilitation Services in Children With Autism From the Perspective of Their Occupational Therapists and Parents - Negin Irani; Cyrus Bavar; Navid Mirzakhani Araghi (Shahid Beheshti University of Medical Sciences, 2023)
Background and Aims Autism is a common disorder among children. Physical and architectural factors of rehabilitation centers may affect the quality of rehabilitation. This study aims to investigate the effect of physical and architectural elements of educational and therapeutic spaces on autism rehabilitation.Methods The present analytical-observational research was cross-sectional. This study used the standard Minnesota Questionnaire (MSQ) to assess employees' job satisfaction. The standard sensory profile questionnaire 2 (short form) was employed to determine the sensory function pattern of autistic children aged 3 to 14 years. Finally, a researcher-made questionnaire of architecture quality assessment was used to evaluate the quality of physical space architecture, interior architecture, and standard facilities of educational and therapeutic spaces. In this cross-sectional study, 32 occupational therapists from university and hospital treatment centers, welfare centers, and private clinics, and 50 parents of children with autism participated as the available sample group. The Pearson correlation coefficient was used to examine the relationship between variables.Results Findings from the study population showed significant relationships between the variables studied in the groups of sensation seeking, sensation avoiding, sensation sensitive, and sensation register (from the analysis of sensory profile) and improving the quality of rehabilitation of children with autism (P<0.05).Conclusion According to the study findings, job satisfaction, physical factors, sensory processing, and assessing the quality of architecture in the design of educational and therapeutic spaces of rehabilitation centers for children with autism are of particular significance. Utilizing the factors studied in this study will not only positively affect the treatment process of these patients, but it will also increase the job satisfaction of occupational therapists working in rehabilitation centers for autism.